Messengers in the Creative Work of Journalists - M. N. Kim (Управленческое консультирование)
In the article the author dwells on the problems of the influence of messengers on the nature of internal communication in the editorial team. There introduce the interviews with the journalists of urban and regional media about the use of messengers in the organization of the editorial work; about new technical possibilities of this type of contact; about use of messengers in the creative work of journalists and more. Also, in the article touches upon the main methods of use messengers in solving editorial tasks: in coordination the actions of journalists; in organizing various group chats; in establishing effective working communications.